Technology of optimization: An emerging configuration of productivity among professional software employees. - Ciccone, Vanessa (European Journal of Cultural Studies, 2022)
In this article, I draw from several months of fieldwork from 2019 to assess professional subjectivity in the software industry of Canada. I assess employees' constructions of and feelings about their own productivity. I argue that the ways in which subjects understand and feel about their productivity says a great deal about how power is 'willfully' negotiated within everyday professional tech settings of neoliberal societies. My findings suggest that optimization is emerging as a technology of self among the individuals I studied, and bringing political consequences. In the first section of the article, I provide a brief overview of the productivity imperative's cultural trajectory, and show its relation to optimization. Then, in the empirical analysis and discussion, I outline that the technology of optimization involves a discourse around bringing one's best to public and private realms, offering a specific set of moral ideals. I then show that another facet of this technology of self is centered on willfully entangling public and private life. Finally, I theorize subjects' reported feelings about their own productivity, assessing how the technology of optimization relates to a politics of privilege. With this study, I seek to make a contribution to the relation between the culture of productivity and professional subjectivity in the software industry, in an effort to expose how power is negotiated at the level of the self in an increasingly influential sector.